-20.5=y/6-1.3

Simple and best practice solution for -20.5=y/6-1.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20.5=y/6-1.3 equation:



-20.5=y/6-1.3
We move all terms to the left:
-20.5-(y/6-1.3)=0
We get rid of parentheses
-y/6+1.3-20.5=0
We multiply all the terms by the denominator
-y+(1.3)*6-(20.5)*6=0
We add all the numbers together, and all the variables
-1y-115.2=0
We move all terms containing y to the left, all other terms to the right
-y=115.2
y=115.2/-1
y=-115+0.2/1

See similar equations:

| -2x-6=50 | | 40x^2+80x-70=0 | | 3b-5=2b÷6+2 | | 8x-5=5x-26 | | 8z^2-2=-8z | | -8p=-3p+10 | | 2x+71=50 | | c-11/3=2 | | 8q^2+3=0 | | 21x+21=777 | | 2+12x+3=136 | | 2z-8=7+5z | | 2s^2=-8s-8 | | 12=3(d+1) | | 16w^2-84w+63=0 | | 5=2(3+2x) | | 5x+90=120 | | 8s^2+7s+5=0 | | -6y=-5y-10 | | 5x+90=12 | | 4.1+x/5=-8.4 | | -3+w=-9-w | | 6q^2+6q=0 | | 7x-(-13)=20 | | 7(x-5)=6(x-2) | | 8d=9d-5 | | 2.5x-4=x+5 | | 9p^2=2 | | 8d=9d−5 | | -9r-5=9-7r | | 1=t-10/2 | | 14x-30=2(7x-15) |

Equations solver categories